Simulation on High Strain Rate Thermal Deformation Constitutive Equation of AZ91 Magnesium Alloy. (1st March 2023) - He, Zhongtao; Xu, Chun
Abstract: The hot compression simulation experiment of AZ91 magnesium alloy was carried out by a Gleeble-1500D thermal simulation machine under the conditions of T within the range of 300~400°C, ε ˙ within the range of 10 -2 ~10 1 s −1, and a compression capacity being 70%. In order to establish the constitutive equation more accurately, this paper uses the piecewise function model to match the σ-ε curve as the necessity of making the simulated curve have a good match with the true stress-strain curve. The linear function and nonlinear function are used to match the σ-ε curve when the material reaches the stage of softening. The fitting results show that the piecewise function matches the true stress-strain curve well under different experimental circumstances of T and ε ˙ even at a high strain rate. This indicates that the piecewise function has a better capacity in the real situation of the relationship between hot-working deformation and the stress-strain curve of magnesium alloys.